Efficacy of organic and inorganic mulching materials on weed count, growth, and yield of aonla (Emblica officinalis) cv. NA 7 - IQBAL, MUDASIR; BAKSHI, PARSHANT; WALI, V K; KUMAR, RAKESH; BHAT, DEEPJI; JASROTIA, AMIT (The Indian Journal of Agricultural Sciences, 2016)
Studies were carried out in NA 7 cultivar of aonla (Emblica officinalis Gaertn) to assess the efficacy of organic and inorganic mulching materials on growth, flowering and yield during 2013 and 2014. Treatments consisted of mulching materials, viz. black polythene, white polythene, paddy straw, saw dust, sarkanda, dry grass with control (unmulched). The results indicated that maximum increase in tree height (0.55 m), tree spread in north-south (0.23 m) and east-west (0.17 m) and tree volume (11.11 cm3) was recorded in black polythene mulch, while it was minimum in control. The black polythene mulch reduced the weed growth in terms of count and weight by cent per cent. As far as floral characteristics, plant with black polythene mulch were the first to flower (11 April 2013), with maximum duration of flowering (23 days) and male : female flower ratio (22:1). Black polythene mulch was superior to all other mulching treatments in terms of yield attributes as it registered maximum fruit set (56.15%), minimum fruit drop (55.87%) and higher yield/tree (72.77 kg/tree). Thus, it can be concluded that black polythene improved the tree growth, flowering, fruit production and lowered weed population of aonla cv. NA 7 as compared to control in rainfed areas.